Accelerating wound healing by biomineralizing crystallization formed from ZIF-8/PLA nanofibers with enhanced revascularization and inflammation reduction - Wang, Xiangsheng; Zhang, Xueer; Wang, Bingqian; Tan, Zhixiang; Chen, Mulan; Shen, Haiyan; Cheng, Hanxiao; Zhou, Zhentao; Zhu, Zhanyong; Guo, Jing; Zhang, Jufang (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionPolylactic acid (PLA) is a synthetic polymer material with good biodegradability, biocompatibility, and bioabsorbability, electrospinning is a convenient and efficient method for preparing PLA nanofibers as wound dressing. However, PLA nanofibers as wound dressings lack biological functions, including promoting angiogenesis, extracellular matrix secretion and regulating inflammation, which are crucial for skin regeneration. Herein, we aimed to develop an effectively methods to enhance biological activity of PLA nanofibers through biomimetic mineralized induced by Zeolite imidazolate framework-8 (ZIF-8) for promoting wound healing.MethodsThe ZIF-8/PLA nanofibers were prepared by electrospinning and immersed in simulated body fluids (SBF) to obtain mineralized PLA nanofibers (mZIF-8/PLA). The physicochemical and mechanical properties, Ions releases, and biocompatibility of the mZIF-8/PLA nanofibers were evaluated in vitro. The regeneration capability of the nanofibers was systemically investigated in vivo using the excisional wound-splinting model in Rats.ResultsHydroxyapatite-like crystals was observed on the surface of nanofibers, EDS-mapping confirmed that the crystal deposits in mZIF-8/PLA nanofibers are composed of calcium, phosphorus, and zinc elements. The mineralized crystallization increased the roughness of PLA nanofibers by altering its surface topography, and significantly improved its mechanical property and hydrophilicity. Biomimetic mineralized mZIF-8/PLA nanofibers significantly improve the biological activity for promoting fibroblast proliferations. The Zinc and calcium ions released from hydroxyapatite-like crystals induced by ZIF-8 also promotes angiogenesis, enhances extracellular matrix deposition and reduces inflammatory infiltration in wound healing model.ConclusionsIn summary, this study demonstrates that mineralized ZIF-8/PLA nanofibers could promote wound healing through regulating angiogenesis and reducing inflammatory response.